Standard measurement method for normal state resistance and critical current of resistively shunted Josephson junctions. (1st April 2022) - Ohkubo, M; Uehara, G; Beyer, J; Mimura, M; Tanaka, H; Ehara, K; Tanaka, S; Noguchi, T; Mitchell, E E; Foley, C P; Fagaly, R L
Abstract: An important parameter of Josephson junctions (JJs) is the product of normal state resistance ( R n ) and critical current ( I c ) for designing superconductor analogue devices or digital circuits. Determination of R n and I c from voltage – current ( U–I ) characteristic curves often faces difficulties; in particular I c is considerably reduced by intrinsic thermal or extrinsic electrical noises. Here, we propose a standard measurement method of R n and intrinsic critical current ( I ci ) for high- T c superconductor (HTS) grain boundary JJs operated in liquid nitrogen and low- T c superconductor (LTS) multilayer superconductor/normal-conductor/superconductor (SNS) JJs in liquid helium. The applicable condition of this method is that both HTS and LTS JJs have U–I curves compatible with resistively-shunted junction (RSJ) model. Both R n and I ci values are extracted by combining a geometric mean criterion to select a data set and a least-squares fitting method with the RSJ model, eliminating two distortion effects on U–I curves: noise-rounding and self-heating. The combined method ensures relative standard uncertainty values of 1.9% for R n and 8% for I ci or better, when the users follow the standard protocol. It is demonstrated that the combined method is valid for d -wave HTS JJs near 77 K, regardless of peculiarities such as 0– π junction transition in d -wave superconductors at lower temperatures, and s -wave LTS SNS JJs with a wide range of junction parameters. This work is the first step to facilitate standardization for superconductor electronics with JJs.